Smart Money Moves: The Relationship Between Technological Progress, Financial Literacy and Lifestyle with Gender as Moderating Variable - Erin, Erin; Zakiatul, Zulfa (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to prove the extent to which the level of financial literacy affects personal financial management, then also to find out the influence of lifestyle and the role of technological advancement. In addition, it is also to find out the role of gender in moderating the relationship between financial literacy, lifestyle, and technological advances with financial management. The method used is a mixed method, namely Quan-Qual. The data used is primary data, collected through direct questionnaire distribution and also conducting direct interviews with respondents while secondary data is in the form of scientific articles and other data that are used as references. The population in this study is the entire population in Muara Enim Regency. Samples were collected using convenience sampling techniques, statistical test tools using Structural Equation Modelling (SEM) with SmartPLS software. The results of the study show that technological advances, lifestyles, and gender have an effect on personal financial management while financial literacy has no effect on personal financial management. The moderation variable, namely gender, had no effect on each of the independent variables in this study.